TEACHING ACROSS THE DIVIDE: PERCEIVED BARRIERS TO THE MOVEMENT OF TEACHERS ACROSS THE TRADITIONAL SECTORS IN NORTHERN IRELAND. Issue 2 (4th March 2021) - Milliken, Matthew; Bates, Jessica; Smith, Alan
ABSTRACT: The community separation of the school system in Northern Ireland limits opportunities for daily cross-community interaction between young people. The deployment pattern of teachers is largely consistent with this divide. Pupils are therefore unlikely to be taught by a teacher from a community background other than their own. Nonetheless, recent research has shown that an increased proportion of teachers are diverting from the community consistent path and are teaching in a school not associated with their own community identity, although this remained a very uncommon choice. Narrative interviews with a purposive sample of these 'cross-over' teachers provide illustrations of the factors that preserve the separation of the teaching profession by community identity. Thematic analysis of this data reveals that policy, perceptions and practice combine to restrict the possibility of cross-community career movement by teachers. If the out-workings of community division in Northern Ireland are to be addressed, then these issues will need to be considered, and actions taken to mitigate this segregation.